1984
DOI: 10.1055/s-2007-1014745
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Obesity to Diabetes

Abstract: In a representative sample of 201 diabetic patients of Tripoli, Libya, 138 were obese. The highest percent of diabetics and obese belong to the age group 41-50 years. In all age groups, there was a parallel increase/decrease in obesity with diabetes. Regulation of body weight should be considered very important in control of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 2 publications
(2 reference statements)
0
3
0
Order By: Relevance
“…Although an increase in the prevalence of obesity has been reported in many countries around the world, the rate of increase in Libya has been observed to be particularly high. The prevalence of obesity in Libya has more than doubled in the last three decades, from 12.6% in 1984 to 30.5% in 2009 [11, 16, 22–25]. Consequently, it may be concluded that the prevalence of obesity in Libya had increased by more than a third over the previous six years from 2009 when it was 30.5% until this year 2016 when it was estimated to be 42.4% in this study.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…Although an increase in the prevalence of obesity has been reported in many countries around the world, the rate of increase in Libya has been observed to be particularly high. The prevalence of obesity in Libya has more than doubled in the last three decades, from 12.6% in 1984 to 30.5% in 2009 [11, 16, 22–25]. Consequently, it may be concluded that the prevalence of obesity in Libya had increased by more than a third over the previous six years from 2009 when it was 30.5% until this year 2016 when it was estimated to be 42.4% in this study.…”
Section: Discussionmentioning
confidence: 57%
“…Libya is following the trend observed in developing countries of steadily becoming more obese, such that obesity in Libya has reached epidemic proportions in the twenty-first century; within all ages obesity is continuing to grow [11, 16, 22–24]. The obesity rate (BMI ≥30 kg/m 2 ) has more than doubled in the last three decades, from 12.6% in 1984 to 30.5% in 2009, while the prevalence of overweight (BMI ≥25 kg/m 2 ) has more than tripled from 19.5 % in 1984 to 63.5 % in 2009 [11, 16, 22–25]. Accordingly, Libya was ranked 35 th on the list of the world's fattest countries based on this last estimation, in 2009 [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation